Coating agents and laminates
Patent Information
- Application Number
- JP2025060003
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0008】 本発明によれば、厚みが薄くても良好な難燃性を有するコート層を形成するコーティング剤及び当該コート層を備える積層体を提供することができる。
Smart Images

Figure 2026166807000001 
Figure 2026166807000002 
Figure 2026166807000003
Abstract
Description
[Technical Field]
[0001] This invention relates to coating agents and laminates. [Background technology]
[0002] Polyurethane foam, made from urethane resin, an organic resin, is used as an insulating material in various structures such as ceilings, roofs, and walls of buildings, including apartment buildings, detached houses, and commercial buildings, due to its excellent heat insulation properties. However, polyurethane foam insulation has the drawback of being highly flammable. Therefore, as a solution to this drawback, a flame-retardant coating layer is being considered (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2013-018911 [Patent Document 2] Japanese Patent Publication No. 2023-013033 [Overview of the project] [Problems that the invention aims to solve]
[0004] However, if the layered coating is too thin, heat can transfer to the underlying urethane insulation and cause it to burn. Therefore, to improve flame retardancy, we considered increasing the thickness of the coating to a certain level or higher. However, attempting to apply a thicker coating would increase the application time and worsen work efficiency.
[0005] Therefore, the object of the present invention is to provide a coating agent that forms a coating layer having good flame retardancy even when thin, and a laminate equipped with said coating layer. [Means for solving the problem]
[0006] The inventors of the present invention have found that the above problems can be solved by forming a coating layer with a coating agent of a specific formulation containing expansive graphite, and have completed the present invention described below. In other words, the present invention provides the following [1] to
[14] .
[0007] [1] A coating agent comprising calcium compounds, silicon-based materials, glass fibers, and expansive graphite. [2] The coating agent according to [1], wherein the calcium-based compound comprises at least one selected from the group consisting of calcium carbonate, calcium oxide, and calcium sulfate. [3] The coating agent according to [1] or "2", wherein the silicon-based material comprises at least one selected from the group consisting of silicon dioxide, mica, and silicates. [4] A coating agent according to any one of [1] to [3], further comprising a metal hydroxide. [5] The coating agent according to [4], wherein the metal hydroxide comprises at least one of aluminum hydroxide and magnesium hydroxide. [6] A coating agent according to any one of [1] to [5], further comprising an adhesion promoter. [7] The coating agent according to [6], wherein the adhesion agent is at least one selected from the group consisting of vinyl copolymer resin, acrylic copolymer resin, methacrylic copolymer resin, epoxy resin, rubber resin, silicone resin, and ethylene-vinyl acetate copolymer resin. [8] A laminate comprising an organic resin layer and a coating layer laminated on the organic resin layer, wherein the coating layer is formed from a coating agent according to any one of [1] to [7]. [9] The laminate according to [8], wherein the organic resin layer is a foam.
[10] The laminate according to [8] or [9], wherein the organic resin layer comprises a urethane resin.
[11] The laminate according to any one of [8] to
[10] , wherein the organic resin layer is applied by spraying.
[12] The laminate according to any one of [8] to
[11] , comprising a primer layer between the organic resin layer and the coat layer.
[13] The laminate according to
[12] , wherein the primer layer contains at least one selected from the group consisting of vinyl copolymer resins, acrylic copolymer resins, methacrylic copolymer resins, epoxy resins, rubber resins, silicone resins, and ethylene-vinyl acetate copolymer resins.
[14] The laminate according to any one of [8] to
[13] , wherein the thickness of the coat layer is 10 mm or less.
Effects of the Invention
[0008] According to the present invention, it is possible to provide a coating agent that forms a coat layer having good flame retardancy even with a small thickness, and a laminate provided with the coat layer.
Modes for Carrying Out the Invention
[0009] Hereinafter, the present invention will be described with reference to embodiments.
[0010] (Coating agent) The coating agent of the present invention contains a calcium-based compound, a silicon-based material, glass fibers, and expandable graphite. Hereinafter, each component will be described in detail.
[0011] [Calcium-based compound] By containing the calcium-based compound and the silicon-based material, the coating agent can form a coat layer with improved flame retardancy of the coat layer formed from the coating agent.
[0012] Examples of calcium-based compounds include calcium carbonate, calcium oxide, calcium sulfate, calcium gluconate, tricalcium silicate, dicalcium silicate, calcium hydroxide, pearl calcium, calcium lactate, milk calcium, shell calcium, calcium acetate, calcium nitrate, calcium bicarbonate, calcium sulfite, tricalcium aluminate, and tetracalcium iron aluminate. Calcium-based compounds may be used individually or in combination of two or more. The coating agent may use a calcium-based compound as a binder, as described later, or it may use a binder in combination with a calcium-based compound other than the binder.
[0013] [Silicon-based materials] Examples of silicon-based materials include silicon-based materials other than glass fibers, as described later, such as silicon dioxide, mica, silicates, silicon nitride, tricalcium silicate, dicalcium silicate, and silicon carbide. As silicon dioxide, mineral compounds such as perlite may be used. Silicon-based materials may be used individually or in combination of two or more. The coating agent may use the binder described later as a silicon-based material, or the binder may be used in combination with a silicon-based material other than the binder. Furthermore, the coating agent may be tricalcium silicate, dicalcium silicate, etc., which are both silicon-based materials and calcium-based compounds. In this specification, the term is used to describe cases where only such compounds are included, as well as cases where both calcium-based compounds and silicon-based materials are included.
[0014] [Binder] The coating agent of the present invention preferably contains a binder. The binder improves the mechanical strength of the coating layer formed by the coating agent. By using an inorganic binder, the coating layer can be made an inorganic coating layer. Using an inorganic binder further improves fire resistance. The inorganic binder is not particularly limited, but examples include water-hardening cement and dolomite plaster. Examples of the water-hardening cement include Portland cement, white cement, blast furnace cement, silica cement, and fly ash cement. Among these, Portland cement, white cement, and dolomite plaster are preferred as binders, and among these, Portland cement and dolomite plaster are preferred. The binder may be used alone or in combination of two or more types. The binder may be a calcium-based compound, a silicon-based material, or a combination of both. For example, in the case of water-hardening cement, it will also consist of calcium-based compounds such as tricalcium silicate and dicalcium silicate, and silicon-based materials.
[0015] The binder content in the coating agent is preferably 10 to 80% by mass, more preferably 15 to 70% by mass, and even more preferably 20 to 55% by mass, based on the total amount of the coating agent. If the binder content is above the lower limit, the mechanical strength of the coating layer is improved. If the binder content is below the upper limit, thermal distortion during heating is less likely to occur, making it easier to prevent damage. In this specification, the total amount of coating agent refers to the amount based on solid content, excluding volatile components such as the diluent described later.
[0016] As described above, calcium-based compounds may be used in the coating agent in addition to the binder. As the calcium-based compound other than the binder, any of the calcium-based compounds listed above may be appropriately selected and used, but at least one selected from calcium carbonate, calcium oxide, and calcium sulfate is preferred, with calcium carbonate being more preferred. The content of calcium-based compounds other than binders in the coating agent is preferably 5 to 40% by mass, more preferably 10 to 30% by mass, and even more preferably 15 to 20% by mass, based on the total amount of the coating agent. If the content of calcium-based compounds is above the lower limit, the flame retardancy of the coating layer formed by the coating agent tends to improve. If the content of calcium-based compounds is below the upper limit, the applicability and other properties improve, and it becomes easier to form a uniform coating layer on the organic resin layer.
[0017] Furthermore, the coating agent may also be a silicon-based material other than the binder. As the silicon-based material other than the binder, any of the silicon-based materials listed above may be appropriately selected and used, but it is preferable to use at least one selected from the group consisting of silicon dioxide, mica, and silicates, with silicon dioxide being particularly preferred. The content of silicon-based materials other than the binder in the coating agent is preferably 2 to 20% by mass, more preferably 4 to 15% by mass, and even more preferably 6 to 10% by mass, based on the total amount of the coating agent. If the content of silicon-based materials is above the lower limit, the flame retardancy of the coating layer formed by the coating agent tends to improve. If the content of silicon-based materials is below the upper limit, the applicability is improved, and it becomes easier to form a uniform coating layer on the organic resin layer.
[0018] [Glass fiber] By including glass fibers, the coating agent can help prevent cracking and maintain the shape of the coating layer formed by the coating agent, thereby creating a more flame-retardant coating layer. The glass fibers are short fibers and are appropriately dispersed in the coating agent and the coating layer formed by the coating agent, and may be intertwined with each other. Glass fibers are what are known as short fibers, and the average fiber length of the glass fibers is not particularly limited, but is preferably 1 to 40 mm, more preferably 3 to 30 mm, and even more preferably 4 to 20 mm. When the average fiber length of the glass fibers is within the above range, the glass fibers become more likely to intertwine with each other, which can contribute to preventing cracking of the coating layer and maintaining its shape. The fiber length of glass fibers can be measured using image analysis such as microscope photographs, or using measuring instruments such as rulers or calipers.
[0019] The glass fiber content in the coating agent is preferably 0.5 to 10% by mass, more preferably 0.7 to 5.0% by mass, and even more preferably 1.0 to 3.0% by mass, based on the total amount of the coating agent. When the glass fiber content is above the lower limit, it contributes to preventing cracking and maintaining the shape of the coating layer formed by the coating agent, thereby improving the flame retardancy of the coating layer. When the glass fiber content is below the upper limit, the applicability is improved, and it becomes easier to form a uniform coating layer on the organic resin layer.
[0020] [Expandable graphite] Expandable graphite is graphite that expands in volume when heated. When a fire breaks out, expandable graphite expands to form an insulating layer, thereby providing excellent heat insulation to the coating layer and improving the flame retardancy of the laminate with the coating layer. Expandable graphite is a conventionally known substance that expands when heated. It is produced by treating powders of natural scaly graphite, pyrolysis graphite, quiche graphite, etc., with an inorganic acid and a strong oxidizing agent to generate graphite intercalation compounds, and is a type of crystalline compound that maintains the layered structure of carbon. Examples of inorganic acids include concentrated sulfuric acid, nitric acid, and selenic acid. Examples of strong oxidizing agents include concentrated nitric acid, persulfates, perchloric acid, perchlorates, permanganates, dichromates, and hydrogen peroxide. The thermally expandable graphite obtained by acid treatment as described above may be further neutralized with ammonia, aliphatic lower amines, alkali metal compounds, alkaline earth metal compounds, etc.
[0021] The expansion initiation temperature of expandable graphite is preferably 100°C or higher. While the coating layer formed from the coating agent may expand due to prolonged heating during use in high-temperature environments, setting the expansion initiation temperature to 100°C or higher prevents such problems. The expansion initiation temperature of expandable graphite is preferably 120°C or higher, and more preferably 140°C or higher. There is no particular upper limit to the expansion initiation temperature of expandable graphite, but from the viewpoint of preventing the expansion initiation of the coating layer formed from the coating agent from being delayed too much and improving the fire-resistant properties of the coating layer formed from the coating agent, 300°C is preferred, 280°C is more preferred, and 240°C is even more preferred. Furthermore, the degree of expansion of expandable graphite is not particularly limited, but is, for example, 50 times or more, preferably 100 times or more. By setting the degree of expansion to be above the lower limit above, a suitable insulating layer can be formed when heated, and flame retardancy is improved. Also, the degree of expansion of expandable graphite is, for example, 500 times or less, preferably 400 times or less. The degree of expansion of expandable graphite is the expansion ratio when heated to 500°C, and can be measured, for example, by placing 0.2g in a test quartz test tube (inner diameter 15mm, capacity 25mL), heating it at 500°C for 5 minutes, and measuring the height.
[0022] The content of expansive graphite in the coating agent is preferably 1 to 20% by mass, more preferably 2 to 15% by mass, and even more preferably 3 to 10% by mass, based on the total amount of the coating agent. If the content of expansive graphite is above the lower limit, the heat insulation properties of the coating layer formed by the coating agent will be good, and the flame retardancy of the laminate having the coating layer will be improved. If the content of expansive graphite is below the upper limit, the applicability will be good, and it will be easier to form a uniform coating layer on the organic resin layer.
[0023] [Metal hydroxide] The coating agent of the present invention may contain a metal hydroxide. By containing a metal hydroxide, the flame retardancy of the coating layer formed by the coating agent is more easily improved.
[0024] Examples of metal hydroxides include aluminum hydroxide, magnesium hydroxide, and calcium hydroxide. Among these, it is preferable to include at least one of aluminum hydroxide and magnesium hydroxide, and more preferably aluminum hydroxide. Including aluminum hydroxide can lower the initial and total heat generation, thereby improving the flame retardancy of the laminate. The metal hydroxide may be used alone or in combination of two or more types.
[0025] The metal hydroxide content in the coating agent is preferably 10 to 50% by mass, more preferably 15 to 45% by mass, and even more preferably 20 to 40% by mass, based on the total amount of the coating agent. If the metal hydroxide content is above the lower limit, the flame retardancy of the coating layer formed by the coating agent tends to improve. If the metal hydroxide content is below the upper limit, the applicability is improved, and it becomes easier to form a uniform coating layer on the organic resin layer.
[0026] [Adhesion-enhancing agent] The coating agent may further contain an adhesion promoter. By including an adhesion promoter, the adhesion strength of the coating layer to the organic resin layer such as polyurethane foam can be increased, allowing the coating layer to be directly laminated onto the organic resin layer such as polyurethane foam. For example, after the laminate is applied to the surface of a building, the coating layer becomes less likely to peel off, and it becomes easier to maintain good flame retardancy. Examples of adhesion promoters include vinyl copolymer resins, acrylic copolymer resins, methacrylic copolymer resins, epoxy resins, rubber resins, silicone resins, and organic adhesion promoters such as ethylene-vinyl acetate copolymer resins. Including these components in the adhesion promoter improves the adhesion of the coating layer. Among these, components obtained by polymerizing double bonds, such as vinyl copolymer resins, acrylic copolymer resins, methacrylic copolymer resins, and ethylene-vinyl acetate copolymer resins, are preferred. Adhesion-enhancing agents may be used individually or in combination of two or more types.
[0027] The content of the adhesion promoter in the coating agent is not particularly limited, but is preferably 1 to 40% by mass, more preferably 3 to 20% by mass, and even more preferably 4 to 10% by mass, based on the total amount of the coating agent. If the content of the adhesion promoter is above the lower limit, sufficient adhesion to the coating layer is easily imparted. If the content of the adhesion promoter is below the upper limit, the applicability is improved, and it becomes easier to form a uniform coating layer on the organic resin layer. Furthermore, by keeping the content below the upper limit, the decrease in the flame retardancy of the coating layer due to the addition of the adhesion promoter can be suppressed. In addition to the components mentioned above, the coating agent may also contain other additives such as pigments, rust inhibitors, and dust inhibitors.
[0028] The coating agent may be diluted with a diluent such as water or an organic solvent, and is preferably diluted with water. The amount of coating agent mixed with the diluent is, by mass, preferably 40 to 400 parts by mass, more preferably 60 to 300 parts by mass, and more preferably 70 to 250 parts by mass, per 100 parts by mass of the diluent. When the mixing amount is within the above range, for example, the viscosity of the coating agent becomes suitable for application, and it becomes easier to form a uniform coating layer on an organic resin layer such as polyurethane foam. The coating agent can be manufactured by mixing the above components and solvents using known methods. Alternatively, the coating agent may be further diluted with a diluent such as water.
[0029] (Laminated structure) The laminate of the present invention comprises an organic resin layer and a coating layer laminated on the organic resin layer. Each component will be described in detail below.
[0030] [Organic resin layer] The organic resin layer constituting the laminate of the present invention can be made of various known resins, such as urethane resin, phenolic resin, styrene resin, polyvinyl chloride (PVC) resin, polyolefin resin, etc., and preferably urethane resin.
[0031] The organic resin layer of the present invention is a foam made of an organic material. The foam made of an organic material is preferably one selected from the group consisting of polyurethane foam, phenol foam, styrene foam, PVC foam, and polyolefin foam such as polyethylene foam, and among these, polyurethane foam is more preferred.
[0032] <Polyurethane foam> In the present invention, the polyurethane foam as the organic resin layer is preferably a polyurethane foam formed from a urethane resin composition containing a polyol, polyisocyanate, a blowing agent, and a catalyst. The foam is preferably a spray foam formed by spraying, as described later, and also preferably a rigid polyurethane foam. The urethane resin composition will be described in more detail below.
[0033] <Polyol> The polyols used in the urethane resin composition are not particularly limited, but examples include polyether polyols and polyester polyols. From the viewpoint of improving the flame retardancy of the polyurethane foam, it is preferable that the polyols include polyester polyols. The polyols may be used individually or in combination of two or more types. From the viewpoint of flame retardancy, it is preferable that the amount of polyester polyol be 20 parts by mass or more, more preferably 50 parts by mass or more, even more preferably 80 parts by mass or more, and particularly preferably 100 parts by mass out of 100 parts by mass of polyol.
[0034] The average hydroxyl value of the polyol used in the present invention is preferably 100 to 500 mg KOH / g, more preferably 150 to 450 mg KOH / g, and even more preferably 180 to 400 mg KOH / g, from the viewpoint of improving the flame retardancy of the polyurethane foam. The average hydroxyl value is the hydroxyl value of a single polyol if only one type of polyol is used, and the average value of hydroxyl groups according to the blending ratio of the two or more polyols if two or more types of polyols are used. For example, when using two types of polyols, (d1) and (d2), if the hydroxyl value of polyol (d1) is X1, the mixing ratio is m1, the hydroxyl value of polyol (d2) is X2, and the mixing ratio is m2, then the average hydroxyl value is expressed by the following formula. Note that the mixing ratio is on a mass basis. Average hydroxyl value (mgKOH / g)=X1×(m1 / (m1+m2))+X2×(m2 / (m1+m2)) The hydroxyl value is measured in accordance with JIS K1557-1:2007.
[0035] <Polyester Polyol> The polyester polyol may be a polyester polyol having an aromatic ring or an aliphatic polyester polyol, but when considering the flame retardancy of the resulting polyurethane foam, it is preferable to use a polyester polyol having an aromatic ring. The polyester polyol having an aromatic ring is preferably a condensate of an aromatic dicarboxylic acid such as o-phthalic acid (phthalic acid), m-phthalic acid (isophthalic acid), p-phthalic acid (terephthalic acid), or naphthalenedicarboxylic acid with a glycol. In particular, from the viewpoint of improving the flame retardancy of the polyurethane foam, it is preferable that the polyol includes a phthalic acid-based polyester polyol, which is a condensate of phthalic acid and glycol, and more preferably a p-phthalic acid-based polyester polyol, which is a condensate of p-phthalic acid and glycol. While the glycol is not particularly limited, it is preferable to use a low molecular weight aliphatic glycol known as a component of polyester polyols, such as ethylene glycol, propylene glycol, or diethylene glycol.
[0036] <Polyether polyol> Examples of polyether polyols include polyoxyalkylene polyols obtained by ring-opening addition polymerization of alkylene oxide to an initiator having two or more active hydrogen atoms. Examples of initiators include aliphatic polyhydric alcohols (e.g., glycols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexylene glycol, and cyclohexanedimethanol; triols such as trimethylolpropane and glycerin; tetrafunctional alcohols such as pentaerythritol; highly functional alcohols such as sucrose and sorbitol); aliphatic amines (e.g., alkylenediamines such as ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, and neopentyldiamine; alkanolamines such as monoethanolamine and diethanolamine); and aromatic amines (e.g., aniline, tolylenediamine, xylylenediamine, diphenylmethanediamine, Mannich condensates, etc.). Of these, polyether polyols produced using an initiator having an aromatic ring are polyether polyols having an aromatic ring. For example, polyether polyols produced using an aromatic amine as an initiator are polyether polyols having an aromatic ring. Among polyether polyols having an aromatic ring, tolylenediamine-based polyether polyols and Mannich-based polyether polyols can be suitably used.
[0037] Tolylenediamine-based polyether polyols are tolylenediamine-based polyether polyols manufactured using tolylenediamine as an initiator. The above-mentioned Mannich-type polyether polyols are obtained using the Mannich reaction and are Mannich condensates having two or more hydroxyl groups in the molecule, or polyether polyols obtained by adding alkylene oxide to such Mannich condensates. More specifically, they are Mannich condensates obtained by the Mannich reaction of at least one of phenol and its alkyl-substituted derivatives, formaldehyde and alkanolamines, or polyether polyols obtained by ring-opening addition polymerization of these compounds with at least one of ethylene oxide and propylene oxide.
[0038] <Polyisocyanate> Examples of polyisocyanates include aromatic polyisocyanates, alicyclic polyisocyanates, and aliphatic polyisocyanates. Examples of aromatic polyisocyanates include phenylene diisocyanate, tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, dimethyldiphenylmethane diisocyanate, triphenylmethane triisocyanate, naphthalene diisocyanate, and polymethylene polyphenyl polyisocyanate (polymeric MDI).
[0039] Examples of alicyclic polyisocyanates include cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and dimethyldicyclohexylmethane diisocyanate. Examples of aliphatic polyisocyanates include methylene diisocyanate, ethylene diisocyanate, propylene diisocyanate, tetramethylene diisocyanate, and hexamethylene diisocyanate.
[0040] Among these, aromatic polyisocyanates are preferred from the viewpoint of ease of use and availability, diphenylmethane diisocyanate, polymeric MDI, or mixtures thereof are more preferred, with diphenylmethane diisocyanate being even more preferred, and 4,4'-diphenylmethane diisocyanate being particularly preferred. Polyisocyanates may be used individually or as a mixture of two or more.
[0041] In the present invention, it is preferable that the isocyanate index of the urethane resin composition is 150 or higher. By setting the isocyanate index to 150 or higher, the flame retardancy of the polyurethane foam is improved, and the flame retardancy of the entire laminate is also made more favorable. From this viewpoint, it is preferable that the isocyanate index is 160 or higher, and more preferably 170 or higher. Furthermore, the isocyanate index is not particularly limited, but is preferably 1,000 or less, more preferably 800 or less, and even more preferably 600 or less. When the isocyanate index is below the above upper limit, flame retardancy that is sufficiently commensurate with the manufacturing cost can be obtained.
[0042] The isocyanate index can be calculated using the following method. Isocyanate Index = Equivalents of polyisocyanate ÷ (Equivalents of polyol + Equivalents of water) × 100 Here, each equivalent number can be calculated as follows: • Equivalent weight of polyisocyanate = Amount of polyisocyanate used (g) × NCO content (mass%) / Molecular weight of NCO (moles) × 100 • Equivalent weight of polyol = OHV × Amount of polyol used (g) ÷ Molecular weight of KOH (millimoles) OHV is the hydroxyl value (mgKOH / g) of a polyol. • Equivalent amount of water = Amount of water used (g) / Molecular weight of water (moles) × Number of OH groups in water In the above formulas, the molecular weight of NCO is 42 moles, the molecular weight of KOH is 56,100 millimoles, the molecular weight of water is 18 moles, and the number of OH groups in water is 2.
[0043] <Catalyst> In the present invention, the catalyst incorporated into the urethane resin composition is not particularly limited, but examples include trimerizing catalysts and resinification catalysts. As for the catalyst, it is preferable to use at least a trimerizing catalyst from the viewpoint of improving foaming properties and flame retardancy, and it is more preferable to use both a trimerizing catalyst and a resinification catalyst.
[0044] <Trimerization catalyst> A trimerizing catalyst is a catalyst that promotes trimerization in a urethane resin composition, thereby promoting the formation of isocyanurate bonds. This promotion of trimerization improves the flame retardancy and resistance to flame spread of polyurethane foam. The trimerizing catalyst preferably contains at least one selected from amine-based catalysts, quaternary ammonium salts, and potassium salts, more preferably contains at least one selected from quaternary ammonium salts and potassium salts, and even more preferably contains both quaternary ammonium salts and potassium salts.
[0045] Quaternary ammonium salts Examples of quaternary ammonium salts include quaternary ammonium carboxylates. The carboxylic acid in the quaternary ammonium carboxylate may have one or more carbon atoms, but it is preferable that it has two or more carbon atoms. The carboxylic acid is preferably an aliphatic carboxylic acid, and more preferably a saturated aliphatic carboxylic acid. The number of carbon atoms in the carboxylic acid is, for example, 20 or less, but is preferably 12 or less, and more preferably 8 or less. The carboxylic acid may be linear or have a branched structure, but it is preferable that it has a branched structure. Having a branched structure tends to reduce reactivity with blowing agents such as hydrofluoroolefins due to steric hindrance, thus improving the stability of the polyol composition.
[0046] Suitable specific examples of carboxylic acids in quaternary ammonium carboxylates include 2-ethylhexanoic acid, 2,2-dimethylpropanoic acid, acetic acid, and formic acid. Among these, at least one selected from acetic acid and 2,2-dimethylpropanoic acid is preferred, and 2,2-dimethylpropanoic acid is more preferred.
[0047] In quaternary ammonium carboxylates, the quaternary ammonium ion is preferably a tetraalkylammonium ion or a hydroxyalkyltrialkylammonium ion, and more preferably a tetraalkylammonium ion.
[0048] Each alkyl group in the tetraalkylammonium ion is, for example, an alkyl group having 1 to 4 carbon atoms, preferably an alkyl group having 1 to 2 carbon atoms, and more preferably a methyl group. Specific examples of tetraalkylammonium ions include tetramethylammonium ions and triethylmethylammonium ions.
[0049] Each alkyl group in the hydroxyalkyltrialkylammonium ion is, for example, an alkyl group having 1 to 4 carbon atoms, preferably a methyl group, an ethyl group, or a butyl group. A hydroxyalkyl group is a group in which one of the hydrogen atoms in the alkyl group is substituted with a hydroxyl group, for example, having 1 to 4 carbon atoms, preferably 2 to 4 carbon atoms, and more preferably 3 or 4 carbon atoms. Examples of hydroxyalkyl groups include hydroxyethyl group, hydroxypropyl group, and hydroxybutyl group. Specific examples of hydroxyalkyltrialkylammonium ions include, for example, hydroxybutyltrimethylammonium ions, hydroxypropyltrimethylammonium ions, and hydroxyethyltrimethylammonium ions.
[0050] The ammonium ion in the quaternary ammonium carboxylate is preferably at least one selected from the group consisting of triethylmethylammonium ion, tetramethylammonium ion, hydroxybutyltrimethylammonium ion, and hydroxypropyltrimethylammonium ion, more preferably at least one selected from the group consisting of triethylmethylammonium ion, tetramethylammonium ion, and hydroxybutyltrimethylammonium ion, and even more preferably tetramethylammonium ion.
[0051] Furthermore, suitable specific examples of quaternary ammonium carboxylates include tetramethylammonium acetate, tetramethylammonium 2,2-dimethylpropanoate, triethylmethylammonium 2-ethylhexanoate, and hydroxybutyltrimethylammonium 2-ethylhexanoate. Among these, at least one selected from tetramethylammonium acetate and tetramethylammonium 2,2-dimethylpropanoate is preferred, and tetramethylammonium 2,2-dimethylpropanoate is more preferred, from the viewpoint of facilitating the formation of isocyanurate bonds by the trimer of polyisocyanate and facilitating the imparting of excellent flame retardancy to polyurethane foam. In this invention, quaternary ammonium carboxylates may be used alone or in combination of two or more types.
[0052] Potassium salts Examples of potassium salts include potassium carboxylates. The carboxylic acid in the potassium carboxylate may have 1 or more carbon atoms, preferably 5 or more carbon atoms. The carboxylic acid is preferably an aliphatic carboxylic acid, more preferably a saturated aliphatic carboxylic acid. The number of carbon atoms in the carboxylic acid is, for example, 20 or less, preferably 12 or less, more preferably 8 or less. Further, the carboxylic acid may be linear or have a branched structure, and preferably has a branched structure. With a branched structure, the reactivity with blowing agents such as hydrofluoroolefins tends to decrease due to steric hindrance, so that the stability of the polyol composition is improved.
[0053] Among others, the potassium carboxylate is preferably a potassium carboxylate represented by the following general formula (1). Since the potassium carboxylate represented by the following general formula (1) has appropriate steric hindrance, it can suppress the reaction of decomposing the blowing agent, and can also prevent the decrease in catalytic activity.
[0054]
Chemical Formula
[0055] R in general formula (1) 1 and R 2 each independently represent an alkyl group, specifically preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and even more preferably an alkyl group having 1 to 2 carbon atoms. The alkyl group may be linear or have a branched structure. R 1 , R 2 When the number of carbon atoms is not less than the above lower limit, the steric hindrance increases, so that the reaction of decomposing hydrofluoroolefins can be suppressed. On the other hand, R 1 , and R2 If the number of carbon atoms is below the aforementioned upper limit, steric hindrance does not become too large, thus preventing the reaction from becoming slow. Also, R 3 R represents a hydrogen atom or an alkyl group, with a hydrogen atom being preferred. 3 If the alkyl group is an alkyl group, it is preferably one to six carbon atoms, more preferably one to four carbon atoms, and even more preferably one to two carbon atoms.
[0056] Preferred specific examples of carboxylic acids in potassium carboxylic acid salts include at least one selected from the group consisting of 2-ethylhexanoic acid, 2,2-dimethylpropanoic acid, acetic acid, and formic acid. Furthermore, carboxylic acids as shown in the above general formula (1) are preferred, with 2,2-dimethylpropanoic acid and 2-ethylhexanoic acid being more preferred, and 2-ethylhexanoic acid being even more preferred. In this invention, the potassium carboxylate salt may be used alone or in combination of two or more types.
[0057] The content of the trimerizing catalyst in the urethane resin composition is preferably 2 to 25 parts by mass, more preferably 3 to 20 parts by mass, and even more preferably 4 to 15 parts by mass, per 100 parts by mass of polyol. If the content of the trimerizing catalyst is above the lower limit, trimerization of polyisocyanate occurs more easily, and the flame retardancy of the resulting polyurethane foam is improved. On the other hand, if the content of the trimerizing catalyst is below the upper limit, the reaction becomes easier to control. Furthermore, the trimerizing catalyst contained in the urethane resin composition of the present invention may be used alone or in combination of two or more types.
[0058] Furthermore, while the above-mentioned quaternary ammonium salt and potassium salt may contain only one of them, it is preferable that both be included. The content of the quaternary ammonium salt is preferably 1.5 to 15 parts by mass, more preferably 2 to 10 parts by mass, and even more preferably 2.5 to 8 parts by mass, per 100 parts by mass of polyol. The potassium salt content is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, and even more preferably 1.0 to 5 parts by mass, per 100 parts by mass of polyol.
[0059] <Resin-based catalyst> The catalyst used in this invention preferably includes a metal catalyst as a resinification catalyst. This metal catalyst is generally called a resinification metal catalyst. In this invention, including the above resinification metal catalyst promotes the reaction between the polyol and the polyisocyanate, and in particular, the initial reaction rate can be increased. Furthermore, including the resinification metal catalyst makes it easier to appropriately control the reaction rate between the polyol and the polyisocyanate. From the viewpoint of foaming properties, the above resinification metal catalyst is preferably a bismuth compound containing bismuth or a tin compound containing tin, and a bismuth compound is more preferable. Bismuth compounds have low reactivity to HFO and high storage stability. In addition, they make it easier to achieve good initial activity without reducing the flame retardancy of the polyurethane foam.
[0060] The resin-based metal catalyst containing bismuth or tin is preferably an organic acid metal salt, and more preferably an organic acid bismuth salt. Specifically, examples of organic acid metal salts include metal salts of carboxylic acids. Examples of metal salts of carboxylic acids include bismuth salts and tin salts of carboxylic acids, with bismuth salts of carboxylic acids being more preferred. Bismuth salts of carboxylic acids are even more preferably bismuth salts of carboxylic acids having 5 or more carbon atoms. Having 5 or more carbon atoms in the carboxylic acid provides good stability against blowing agents, especially hydrofluoroolefins. Furthermore, from the viewpoint of catalytic activity, the number of carbon atoms in the carboxylic acid is preferably 18 or less, and more preferably 12 or less. The carboxylic acid is preferably an aliphatic carboxylic acid, and more preferably a saturated aliphatic carboxylic acid. The carboxylic acid may be linear or have a branched structure, but it is preferable to have a branched structure.
[0061] Specific examples of carboxylic acids include octyl acid, lauryl acid, versatic acid, pentanoic acid, and acetic acid, with octyl acid being preferred among these. That is, the resin-based metal catalyst is preferably a metal salt of octyl acid, and more preferably a bismuth salt of octyl acid. These carboxylic acids may be linear as described above, but may also have a branched structure. An example of octyl acid having a branched structure is 2-ethylhexanoic acid. The metal salt of the carboxylic acid may also be a carboxylate salt of an alkyl metal. For example, the tin carboxylate salt may be a dialkyltin carboxylate, and preferably a dioctyltin carboxylate. Specific examples of metal salts of carboxylic acids include bismastrioctate, bismastriacetate, bismastripropionate, bismastriptate, bismastriptate (2-ethylhexanoate), bismastriptate (neodecanate), bismastrilaurate, bismastriolate, bismastriate, dioctyltin versatate, dibutyltin dilaurate, dioctyltin dilaurate, and tin dioctoate. Among the above, bismastrioctate, bismastrictate (2-ethylhexanoate), bismastrictate (neodecanate), and dioctyltin versatate are preferred due to their high catalytic effectiveness and availability, with bismastrictate (2-ethylhexanoate) being more preferred.
[0062] The urethane resin composition of the present invention may also preferably contain a heterocyclic compound having a nitrogen atom (hereinafter also referred to as "nitrogen-containing heterocyclic compound") as a resinification catalyst. Including a nitrogen-containing heterocyclic compound as a resinification catalyst improves stability with respect to hydrofluoroolefins, thereby preventing the decomposition of hydrofluoroolefins and resulting in good foaming properties. Furthermore, it is possible to maintain a reaction rate above a certain level, improving the workability when spraying the urethane resin composition. Among nitrogen-containing heterocyclic compounds, imidazole derivatives are more preferred. As described above, imidazole derivatives are less affected by hydrofluoroolefins and facilitate the reaction between polyols and polyisocyanates while increasing the stability of the polyol composition. Therefore, by containing imidazole derivatives, the reactivity between the polyol and polyisocyanate is enhanced, resulting in even better foaming properties. The imidazole derivative is preferably an imidazole in which the 1st and 2nd positions are independently substituted with alkyl groups having 8 or fewer carbon atoms, and the alkyl groups preferably have 6 or fewer carbon atoms, more preferably 4 or fewer carbon atoms. A suitable specific example of an imidazole derivative is represented by the following general formula (2).
[0063] [ka] (In general formula (2), R 4 and R 5 Each of these independently represents an alkyl group having 1 to 8 carbon atoms or an alkenyl group having 2 to 8 carbon atoms.
[0064] R in general formula (2) 4 and R 5 Each of these independently represents an alkyl group having 1 to 8 carbon atoms or an alkenyl group having 2 to 8 carbon atoms. The alkyl group and alkenyl group may each be linear or have a branched structure. Specific examples of alkyl groups include methyl group, ethyl group, propyl group, isopropyl group, butyl group, isobutyl group, sec-butyl group, pentyl group, neopentyl group, isopentyl group, sec-pentyl group, hexyl group, heptyl group, octyl group, and the like. Specific examples of alkenyl groups include vinyl, 1-propenyl, allyl, isopropenyl, 1-butenyl, 2-butenyl, pentenyl, hexenyl, heptenyl, and octenyl groups. R 4 and R 5 If the number of carbon atoms in the alkyl or alkenyl group is greater than or equal to the lower limit, the steric hindrance increases, making it less susceptible to the effects of blowing agents such as hydrofluoroolefins, which is preferable. On the other hand, R 4and R 5 If the number of carbon atoms in the alkyl group is below the aforementioned upper limit, the steric hindrance does not become excessively large, allowing the reaction between the polyol and polyisocyanate to proceed rapidly, and resulting in good foaming properties. From these perspectives, R 4 and R 5 Each of these groups is preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and even more preferably a methyl group.
[0065] Examples of imidazole derivatives represented by general formula (2) include 1,2-dimethylimidazole, 1-ethyl-2-methylimidazole, 1-methyl-2-ethylimidazole, 1,2-diethylimidazole, and 1-isobutyl-2-methylimidazole. Among these, 1,2-dimethylimidazole and 1-isobutyl-2-methylimidazole are preferred from the viewpoint of improving catalyst activity in the presence of hydrofluoroolefins and promoting rapid reaction. Furthermore, 1,2-dimethylimidazole is even more preferred from the viewpoint of further enhancing stability.
[0066] The content of the resinification catalyst in the urethane resin composition is not particularly limited, but is preferably 1 to 15 parts by mass, more preferably 2 to 10 parts by mass, and even more preferably 3 to 8 parts by mass, per 100 parts by mass of polyol. If the resinification catalyst is above the lower limit, the reaction rate between the polyol and polyisocyanate is increased, making it easier to form a high-quality polyurethane foam. If the resinification catalyst is below the upper limit, the reaction rate between the polyol and polyisocyanate can be appropriately controlled. The bismuth salt content in the urethane resin composition is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 3 parts by mass, and even more preferably 1 to 2 parts by mass, per 100 parts by mass of polyol. When the bismuth salt content is within the above range, it becomes easier to impart excellent flame retardancy to the polyurethane foam, and the laminate becomes less likely to ignite. The imidazole derivative content in the urethane resin composition is preferably 1 to 10 parts by mass, more preferably 2 to 8 parts by mass, and even more preferably 3 to 6 parts by mass, per 100 parts by mass of polyol.
[0067] <Foaming agent> The blowing agent promotes the foaming of the urethane composition. Examples of blowing agents include organic physical blowing agents such as water, low-boiling hydrocarbons such as propane, butane, pentane, hexane, heptane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, and cycloheptane; chlorinated aliphatic hydrocarbon compounds such as dichloroethane, propyl chloride, isopropyl chloride, butyl chloride, isobutyl chloride, pentyl chloride, and isopentyl chloride; ether compounds such as hydrofluoroolefins (hereinafter sometimes referred to as "HFO") and diisopropyl ether; or mixtures of these compounds; and inorganic physical blowing agents such as nitrogen gas, oxygen gas, argon gas, and carbon dioxide gas. Of these, it is preferable to include hydrofluoroolefin (HFO), which has high stability as a blowing agent, is less prone to a decrease in catalytic activity, and also has a low environmental impact.
[0068] Suitable HFOs as blowing agents include fluoroalkenes with approximately 3 to 6 carbon atoms. Alternatively, the HFO may be a hydrochlorofluoroolefin containing a chlorine atom, and therefore may also be a chlorofluoroalkene with approximately 3 to 6 carbon atoms. Examples of HFOs include trifluoropropene, tetrafluoropropene such as HFO-1234, pentafluoropropene such as HFO-1225, chlorodifluoropropene, chlorotrifluoropropene such as HFO-1233, and chlorotetrafluoropropene. More specifically, 3,3,3-trifluoropropene (HFO-1243zf), trans-1,3,3,3-tetrafluoropropene (HFO-1234ze(E)), cis-1,3,3,3-tetrafluoropropene (HFO-1234ze(Z)), 2,3,3,3-tetrafluoropropene (HFO-1234yf), 1,1,3,3-tetrafluoropropene, cis-1,3,3,3-tetrafluoropropene (HFO-1234ze(Z)), and trans-1,2,3,3,3-pene. Examples include tafluoropropene (HFO-1225ye(E)), cis-1,2,3,3,3-pentafluoropropene (HFO-1225ye(Z)), 1,1,3,3,3-pentafluoropropene (HFO-1225zc), 1,1,2,3,3-pentafluoropropene (HFO-1225yc), trans-1-chloro-3,3,3-trifluoropropene (HFO-1233zd(E)), and 1,1,1,4,4,4-hexafluorobuto-2-ene (HFO-1336mzz). Among these, HFO-1233zd(E) is preferred.
[0069] The foaming agent content in the urethane resin composition is preferably 10 to 80 parts by mass, more preferably 15 to 70 parts by mass, and even more preferably 20 to 60 parts by mass, per 100 parts by mass of polyol. Furthermore, the HFO content in the urethane resin composition is preferably 10 to 70 parts by mass, more preferably 15 to 60 parts by mass, and even more preferably 20 to 55 parts by mass, per 100 parts by mass of polyol.
[0070] The urethane resin composition may contain blowing agents other than HFO. For example, organic physical blowing agents such as water, low-boiling hydrocarbons such as propane, butane, pentane, hexane, heptane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, and cycloheptane, chlorinated aliphatic hydrocarbon compounds such as dichloroethane, propyl chloride, isopropyl chloride, butyl chloride, isobutyl chloride, pentyl chloride, and isopentyl chloride, ether compounds such as diisopropyl ether, or mixtures thereof, or inorganic physical blowing agents such as nitrogen gas, oxygen gas, argon gas, and carbon dioxide gas can be used. Furthermore, one or more of the above-mentioned foaming agents may be used. In the urethane resin composition of the present invention, it is preferable to use the above-mentioned HFO in combination with other foaming agents. For example, HFO may be used in combination with water, oxygen gas, or carbon dioxide gas, which have excellent handling properties. Water is particularly preferred from the viewpoint of adjusting the isocyanate index and from the viewpoint of ease of handling.
[0071] The water content is preferably 0 to 10 parts by mass, more preferably 0 to 8 parts by mass, and even more preferably 0 to 6 parts by mass, per 100 parts by mass of polyol.
[0072] <Flame retardant> The urethane resin composition preferably contains a flame retardant. Examples of flame retardants include liquid flame retardants and solid flame retardants, and either of these may be used, but it is preferable to include at least a liquid flame retardant. In addition to the liquid flame retardant, a solid flame retardant may also be used.
[0073] <Liquid flame retardant> Liquid flame retardants make it easier to impart excellent flame retardancy to polyurethane foams without excessively increasing the viscosity of the urethane resin composition. Liquid flame retardants are liquid at room temperature (25°C) and normal pressure (1 atm). Examples of liquid flame retardants include phosphate ester-based flame retardants.
[0074] As phosphate ester-based flame retardants, monophosphate esters, condensed phosphate esters, etc., can be used. A monophosphate ester is a phosphate ester that has one phosphorus atom in its molecule. Examples of monophosphate esters include trialkyl phosphates such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, and tri(2-ethylhexyl) phosphate; halogen-containing phosphate esters such as tris(β-chloropropyl) phosphate; trialkoxy phosphates such as tributoxyethyl phosphate; aromatic ring-containing phosphate esters such as tricresyl phosphate, trixylenyl phosphate, tris(isopropylphenyl) phosphate, cresyldiphenyl phosphate, and diphenyl(2-ethylhexyl) phosphate; and acidic phosphate esters such as monoisodecyl phosphate and diisodecyl phosphate.
[0075] Examples of condensed phosphate esters include aromatic condensed phosphate esters such as trialkyl polyphosphates, resorcinol polyphenyl phosphates, bisphenol A polycresyl phosphates, and bisphenol A polyphenyl phosphates. Examples of commercially available condensed phosphate esters include "CR-733S," "CR-741," and "CR747" from Daihachi Chemical Industry Co., Ltd., and "ADEKA Stab PFR" and "FP-600" from ADEKA Corporation.
[0076] The phosphate ester flame retardants may be used individually from the above-mentioned types, or two or more may be used in combination. Among these, monophosphate esters are preferred from the viewpoint of making it easier to adjust the viscosity of the urethane resin composition and from the viewpoint of improving the flame retardancy of the polyurethane foam, and halogen-containing phosphate esters such as tris(β-chloropropyl) phosphate are more preferred.
[0077] The content of the phosphate ester-based flame retardant in the urethane resin composition is not particularly limited, but is preferably 5 to 80 parts by mass, more preferably 10 to 70 parts by mass, and even more preferably 15 to 60 parts by mass, per 100 parts by mass of polyol. If the content of phosphate ester-based flame retardants is above these lower limits, the viscosity of the urethane resin composition can be lowered, and flame retardancy can be easily imparted to the polyurethane foam even without substantially including solid flame retardants. Furthermore, if the content of phosphate ester-based flame retardants is below these upper limits, foaming is not inhibited, making it easier to manufacture the polyurethane foam.
[0078] <Solid flame retardant> Solid flame retardants make it easier to impart excellent flame retardancy to polyurethane foams. Solid flame retardants are solid at room temperature (25°C) and normal pressure (1 atm). Examples of solid flame retardants include red phosphorus-based flame retardants, bromine-containing flame retardants, boron-containing flame retardants, antimony-containing flame retardants, and metal hydroxides. Among these, red phosphorus-based flame retardants are preferred.
[0079] Red phosphorus-based flame retardants may consist of pure red phosphorus, but they may also be coated with a resin, metal hydroxide, metal oxide, etc., or they may be a mixture of red phosphorus and a resin, metal hydroxide, metal oxide, etc. The resin used to coat or mix with red phosphorus is not particularly limited, but examples include thermosetting resins such as phenolic resins, epoxy resins, unsaturated polyester resins, melamine resins, urea resins, aniline resins, and silicone resins. From the viewpoint of flame retardancy, metal hydroxides are preferred as the compound used for coating or mixing. Examples of the above-mentioned metal hydroxides include magnesium hydroxide, calcium hydroxide, aluminum hydroxide, iron hydroxide, nickel hydroxide, zirconium hydroxide, titanium hydroxide, zinc hydroxide, copper hydroxide, vanadium hydroxide, and tin hydroxide.
[0080] When a urethane resin composition contains a solid flame retardant, the amount of solid flame retardant in the urethane resin composition is not particularly limited, but is preferably 5 to 60 parts by mass, more preferably 10 to 50 parts by mass, and even more preferably 20 to 40 parts by mass, per 100 parts by mass of polyol. If the amount of solid flame retardant is above the lower limit, the flame retardancy of the polyurethane foam is improved, and ignition of the laminate can be effectively prevented. If the amount of solid flame retardant is below the upper limit, it prevents the viscosity from becoming excessively high, making it easier to improve the workability of the urethane resin composition, for example, making it easier to improve sprayability.
[0081] <Foam stabilizer> The urethane resin composition may contain a foam stabilizer. Suitable foam stabilizers include compounds having polar and non-polar portions within their molecule and exhibiting surfactant properties. The foam stabilizer is not particularly limited, but examples include surfactants such as polyoxyalkylene foam stabilizers such as polyoxyalkylene alkyl ethers and silicone foam stabilizers such as organopolysiloxanes. As a silicone foam stabilizer, a graft copolymer of polyoxyalkylene glycol, which is a polymer of ethylene oxide or propylene oxide, and polydimethylsiloxane may also be used. Commercially available products can also be used, specifically foam stabilizers such as SH-193 (Dow Toray), S-824-02 (Nippon Unicar), SZ-1704 (Nippon Unicar), F501 (Shin-Etsu Chemical Co., Ltd.), and SF-2937F (Dow Toray). The amount of foam stabilizer is not particularly limited, but is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, and even more preferably 1 to 5 parts by mass per 100 parts by mass of polyol.
[0082] (Other ingredients) In addition to the above, the urethane resin composition may contain, as necessary and within limits that do not impair its purpose, one or more additives selected from phenolic, amine, and sulfur-based antioxidants, inorganic fillers, heat stabilizers, metal damage inhibitors (metal deactivators), antistatic agents, stabilizers, crosslinking agents, lubricants, softeners, plasticizers, pigments, tackifying resins, polybutene, petroleum resins, and other tackifying agents. Inorganic fillers other than solid flame retardants include, for example, silica, diatomaceous earth, alumina, titanium dioxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, ferrites, basic magnesium carbonate, calcium carbonate, magnesium carbonate, barium carbonate, dawsonite, hydrotalcite, calcium sulfate, barium sulfate, potassium salts such as calcium silicate, talc, clay, mica, montmorillonite, bentonite, activated clay, sepiolite, imogolite, sericite, glass beads, silica powder, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon powder, charcoal powder, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum porate, molybdenum sulfide, silicon carbide, various magnetic powders, fly ash, etc.
[0083] Furthermore, a urethane resin composition that is substantially free of fillers is also preferred. By being substantially free of fillers, re-stirring of the polyol composition, etc., described later during application becomes unnecessary, thereby improving workability. In addition, by providing a coating layer formed with the coating agent of the present invention, the flame retardancy of the laminate can be increased even without the presence of fillers. In this specification, "substantially free of fillers" means that the filler content in the urethane resin composition is 5 parts by mass or less per 100 parts by mass of polyol, preferably 3 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0 parts by mass. In this specification, "filler" refers to a component that remains solid in a urethane resin composition without dissolving in polyols and polyisocyanates, and the above-mentioned solid flame retardants and inorganic fillers are included in the definition of filler. However, catalysts are not included in the definition of filler.
[0084] The urethane resin composition of the present invention hardens through a reaction between a polyol and a polyisocyanate, and therefore its viscosity changes over time. For this reason, it is preferable to divide the urethane resin composition into two or more parts before use to prevent it from reacting and hardening, and then combine the two or more parts into one when using the urethane resin composition.
[0085] When dividing a urethane resin composition into two or more parts, the curing reaction should be initiated only after mixing the components of the divided urethane resin composition, rather than each component alone. Preferably, the urethane resin composition is divided into one and two parts to form a two-part curing type. In this case, the urethane resin composition is usually divided into a polyol composition containing a polyol compound and a polyisocyanate composition containing a polyisocyanate.
[0086] The catalyst, blowing agent, flame retardant, and foam stabilizer described above, as well as other additives added as needed, may be contained in the polyol composition. They may also be contained in the polyisocyanate composition, or provided separately from the polyol composition and the polyisocyanate composition, but it is preferable that they be contained in the polyol composition. In other words, the polyol composition is preferably a polyol premix containing a polyol, a catalyst, a blowing agent, a flame retardant, and a foam stabilizer, as well as other additives as needed, and the urethane resin composition of the present invention is preferably a mixture of the polyol premix and a polyisocyanate. Furthermore, it is preferable that the volume of the polyol premix (liquid 1) and the polyisocyanate (liquid 2) mixed with the polyol premix are substantially the same. Specifically, the volume ratio of polyisocyanate to polyol premix is preferably 0.8 to 1.2, more preferably 0.9 to 1.1, and even more preferably 0.95 to 1.05.
[0087] The urethane resin composition begins to react when its components are mixed, such as by mixing liquid 1 and liquid 2. Over time, the viscosity increases, curing and foaming progress, and it loses its fluidity, becoming a polyurethane foam. The urethane resin composition is usually allowed to cure and foam by being left at room temperature (for example, around 10-40°C), but heating may be used if necessary.
[0088] In the present invention, the polyurethane foam is a spray foam formed from the above-described urethane resin composition. In this invention, for example, a polyurethane resin composition is sprayed onto the surface of a structure, and curing and foaming are carried out on the surface of the structure to form a polyurethane foam on the surface of the structure. The structure is not particularly limited, but examples include buildings, furniture, automobiles, trains, ships, etc., but among these, building structures such as walls, ceilings, roofs, and floors are preferred. Spraying can be carried out using a spraying device (e.g., GRACO A-25) and a spray gun (e.g., Gasmar D-gun). Spraying can be carried out, for example, by adjusting the temperature of the polyol premix and polyisocyanate in separate containers within the spraying device, mixing them by collision at the tip of the spray gun, and atomizing the mixture with air pressure. The spraying equipment and spray gun are well-known and commercially available products can be used. Furthermore, the stock solution temperature settings, pressure, etc., can be adapted to general polyurethane foam spraying conditions.
[0089] The thickness of the polyurethane foam is not particularly limited, but is preferably 2 to 150 mm, more preferably 5 to 80 mm, and even more preferably 8 to 50 mm. Having a thickness above these lower limits makes it easier to improve various properties of the polyurethane foam, such as flame retardancy. Conversely, keeping the thickness below these upper limits prevents the polyurethane foam from becoming unnecessarily thick. In the above explanation, we have assumed that urethane foam is used as the organic resin layer. However, it is also possible to use materials other than urethane foam as the organic resin layer. In that case, it is preferable to form the organic resin layer on the surface of the structure or other surface using a known method.
[0090] [Coating layer] The coating layer constituting the laminate of the present invention is formed by the coating agent described above. The coating layer is preferably laminated over the entire surface of the polyurethane foam as an organic resin layer, but it may also be laminated only on a portion of the surface of the polyurethane foam.
[0091] The thickness of the coating layer is not particularly limited, but is preferably 20 mm or less, more preferably 15 mm or less, even more preferably 10 mm or less, and even more preferably 6 mm or less. A coating layer thickness below a certain level improves workability during coating application. It also makes it easier to prevent at least a portion of the coating layer from detaching from the polyurethane foam due to the weight of the coating layer itself after the laminate has been applied. Furthermore, from the viewpoint of flame retardancy, the thickness of the coating layer is preferably 1 mm or more, and more preferably 2 mm or more.
[0092] The coating layer can be formed by applying the above-mentioned coating agent to the surface of the polyurethane foam by methods such as spraying or troweling, and then drying it. If the laminate includes a primer layer as described later, it is preferable to form the coating layer on the surface of the primer layer opposite to the surface in contact with the polyurethane foam.
[0093] (Primer layer) The laminate of the present invention may include a primer layer between the organic resin layer and the coating layer. By including a primer layer, the primer layer acts as an adhesive, making it less likely for the coating layer to detach from the organic resin layer. The primer components that can be used as a primer layer are the same as those used in the adhesion promoters described above, so a detailed explanation is omitted. Additionally, additives may be added to the primer components as appropriate. The thickness of the primer layer is not particularly limited, but is preferably 0.01 to 5 mm, more preferably 0.05 to 3 mm, and even more preferably 0.1 to 1 mm. The primer layer can be formed by applying the primer components described above onto the organic resin layer and allowing them to dry as appropriate. The primer components can be diluted with a solvent or water as appropriate before being applied onto the organic resin layer. Furthermore, the coating layer of the laminate of the present invention may be formed directly on the surface of an organic resin layer such as a polyurethane foam. For example, it is preferable that the coating layer be formed directly on the surface of the organic resin layer when the coating agent contains an adhesion promoter.
[0094] [Method for manufacturing laminates] The laminate of the present invention can be manufactured, for example, by a manufacturing method that includes the steps of forming an organic resin layer and forming a coating layer on the organic resin layer. Furthermore, this manufacturing method may also include the step of forming a primer layer on the organic resin layer, in which case the coating layer should be formed on the primer layer. Details of each step are as described above, so their explanation will be omitted here. [Examples]
[0095] The present invention will be described in more detail below with reference to examples, but the present invention is not limited in any way by these examples.
[0096] [Materials used] (Polyisocyanate) • 4,4'-Diphenylmethane diisocyanate (4,4'-MDI) (manufactured by Manka Chemical Japan, product name: PM200)
[0097] (Polyol) • p-phthalate polyester polyol (manufactured by Kawasaki Chemical Industries, Ltd., product name: Maximol RLK-087, hydroxyl value = 200 mg KOH / g)
[0098] (Liquid flame retardant) • Phosphate ester: Tris(β-chloropropyl) phosphate (manufactured by Daihachi Chemical Co., Ltd., product name: TMCPP)
[0099] (Solid flame retardant) • Red phosphorus (manufactured by Phosphorus Chemical Industry Co., Ltd., product name: Nova Excel 140)
[0100] (Foam stabilizer) • Silicone foam stabilizer (manufactured by Dow Toray, product name: SH-193)
[0101] (catalyst) • Trimerization catalyst 1: Quaternary ammonium salt, tetramethylammonium 2,2-dimethylpropanoate (manufactured by Air Products, product name: DABCO(registered trademark) TMR7), concentration 45-55% by mass • Trimerization catalyst 2: Metal catalyst, potassium 2-ethylhexanoate (Air Products, Inc., product name: DABCO(registered trademark) K-15), concentration 70-80% by mass • Resinization catalyst 1: Bismuth salt, bismastris (2-ethylhexanoate) (manufactured by Nitto Kasei Co., Ltd., product name: Neostan U-600), concentration 55-58% by mass • Resinization catalyst 2: Imidazole derivative, 1,2-dimethylimidazole (TOYOCAT®-DM70, manufactured by Tosoh Corporation), concentration 65-75% by mass
[0102] (Foaming agent) ·water • Hydrofluoroolefin (HFO), trans-1-chloro-3,3,3-trifluoropropene (manufactured by Honeywell Japan, product name: Soltis LBA)
[0103] (Coating agent) • Portland cement (Main components: tricalcium silicate, dicalcium silicate, tricalcium aluminate, tetracalcium iron aluminate; manufactured by Tokuyama Corporation; product name: ordinary Portland cement) • Dolomite plaster (Main component: CaMg(CO3)2, manufactured by Nippon Plaster Co., Ltd., Product name: Dolomite plaster) • Aluminum hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) • Calcium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) • Perlite (manufactured by Mitsui Mining & Smelting Perlite Co., Ltd.) • Glass fiber (manufactured by Morimar SSP Co., Ltd.) • Adhesion enhancer (manufactured by Dancoat, product name: Adhesive 200A)
[0104] [Measurement and evaluation methods for each physical property] (Flame retardant) The cone calorimeter test samples obtained in each example and comparative example were subjected to a radiant thermal intensity test of 50 kW / m² in accordance with the ISO-5660 test method. 2 Total heat output (MJ / m²) when heated for 10 minutes 2 The flame retardancy was evaluated based on the following criteria. The surface with the coating layer was positioned to face the heater used in the cone calorimeter test. The evaluation criteria are as follows: <Evaluation Criteria> 〇: Total heat generation over 10 minutes is 0 MJ / m³ 2 More than 5MJ / m 2 less than △: Total heat generation over 10 minutes is 5 MJ / m³ 2 More than 8MJ / m 2 less than ×: Total heat output over 10 minutes is 8 MJ / m³ 2 Larger than
[0105] (Workability) Using painting equipment, a coating agent is sprayed onto the surface of the polyurethane foam, covering 1m 2The time taken to ensure that the entire coating layer reached a predetermined thickness or greater over the specified area was measured. The evaluation criteria were as follows, and work efficiency was assessed based on the time taken. <Evaluation Criteria> ○: Less than 1 minute △: 1 minute or more, less than 2 minutes ×: More than 2 minutes
[0106] (judgement) The overall evaluation was conducted based on the following evaluation criteria. <Evaluation Criteria> ○: Both flame retardancy and workability were evaluated as "○". △: At least one of the evaluation results for flame retardancy and workability was "△". ×: At least one of the evaluation results for flame retardancy or workability was "×".
[0107] [Example 1] A polyurethane foam was obtained using a urethane resin composition prepared by mixing a polyol composition containing a polyol, a liquid flame retardant, a catalyst, and a blowing agent, according to the formulations shown in Table 1, with a polyisocyanate, under the following conditions. (Sample preparation conditions) • Spraying machine: Graco H-25 spraying device • Settings (Heater settings) Isocyanate heater: 38℃ Premix heater (for heating polyol compositions): 38℃ Hose heater (for pre-mixing heating of polyisocyanate and polyol compositions): 38°C • Base material: Gypsum board • Substrate temperature (temperature of the surface to be sprayed): 25℃±5℃
[0108] As described above, a sample was obtained in which polyurethane foam was formed on a gypsum board. This sample was cut out from the polyurethane foam side to include the gypsum board, with dimensions of 10 cm in length, 10 cm in width, and 5.0 cm in thickness. A portion of the cut-out sample was gypsum board, with the gypsum board thickness being 1.25 cm and the polyurethane foam thickness being 3.75 cm out of the 5.0 cm thickness. Next, apply a primer (a mixture of adhesive 200A and water in a mass ratio of 1:1) to the side of the polyurethane foam opposite to the side in contact with the gypsum board, at a rate of 0.1 to 0.15 kg / m². 2 The coating was applied under these conditions and dried for one day at 25°C. Furthermore, the coating agents listed in Table 1 were mixed with water at a ratio of 150 / 100 (coating agent / water) by mass. The resulting mixture was applied to the primer-coated surface of the polyurethane foam by trowel application, and then dried at 25°C for two weeks to form a coating layer. The thickness of the coating layer after drying was as shown in Table 1. In this way, a sample for cone calorimeter testing was obtained, which included a laminate in which a coating layer was laminated on the surface of a polyurethane foam.
[0109] [Examples 2-6, 8-13] A sample for the cone calorimeter test was prepared in the same manner as in Example 1, except that the composition of the urethane resin composition and the coating agent was changed as shown in Table 1.
[0110] [Example 7] The procedure was carried out in the same manner as in Example 1, except that the composition of the coating agent was changed as shown in Table 1, and the coating agent was applied directly to the polyurethane foam without applying a primer.
[0111] [Comparative Examples 1-3] A sample for the cone calorimeter test was prepared in the same manner as in Example 1, except that the composition of the coating agent was changed as shown in Table 1, and the thickness of the coating layer after drying was also changed as shown in Table 1.
[0112] [Table 1]
[0113] As is clear from the above examples, the laminate of the present invention, having a coating layer formed from a coating agent containing a calcium-based compound, a silicon-based material, glass fibers, and expandable graphite, exhibited good flame retardancy even with a thin coating layer and demonstrated excellent flame retardancy in cone calorimeter tests. In contrast, in Comparative Example 3, excellent flame retardancy could not be achieved because the above-mentioned coating layer was not formed on the polyurethane foam. Also, in Comparative Examples 1 and 2, flame retardancy could be achieved by increasing the thickness of the coating layer, but this resulted in a deterioration of workability.
Claims
1. A coating agent comprising calcium-based compounds, silicon-based materials, glass fibers, and expandable graphite.
2. The coating agent according to claim 1, wherein the calcium-based compound comprises at least one selected from the group consisting of calcium carbonate, calcium oxide, and calcium sulfate.
3. The coating agent according to claim 1, wherein the silicon-based material comprises at least one selected from the group consisting of silicon dioxide, mica, and silicates.
4. The coating agent according to claim 1, further comprising a metal hydroxide.
5. The coating agent according to claim 4, wherein the metal hydroxide comprises at least one of aluminum hydroxide and magnesium hydroxide.
6. The coating agent according to claim 1, further comprising an adhesion promoter.
7. The coating agent according to claim 6, wherein the adhesion agent is at least one selected from the group consisting of vinyl copolymer resin, acrylic copolymer resin, methacrylic copolymer resin, epoxy resin, rubber resin, silicone resin, and ethylene-vinyl acetate copolymer resin.
8. A laminate comprising an organic resin layer and a coating layer laminated on the organic resin layer, A laminate in which the coating layer is formed from a coating agent according to any one of claims 1 to 7.
9. The laminate according to claim 8, wherein the organic resin layer is a foam.
10. The laminate according to claim 8, wherein the organic resin layer contains a urethane resin.
11. The laminate according to claim 8, wherein the organic resin layer is applied by spraying.
12. The laminate according to claim 8, further comprising a primer layer between the organic resin layer and the coating layer.
13. The laminate according to claim 12, wherein the primer layer comprises at least one selected from the group consisting of vinyl copolymer resin, acrylic copolymer resin, methacrylic copolymer resin, epoxy resin, rubber resin, silicone resin, and ethylene-vinyl acetate copolymer resin.
14. The laminate according to claim 8, wherein the thickness of the coating layer is 10 mm or less.
Citation Information
Patent Citations
Coating agent for flameproofing synthetic resin member and the synthetic resin member using the same
JP2013018911A
Organic foam protective structure and method of forming the same
JP2023013033A